Larva monitoring on elementary school students (SD) as prevention of dengue fever (DBD) - Lubis, Sri Novita; CCA, Puteri; A, Lanova Dwi; Salmah, Umi (Talenta Publisher, 2020)
Dengue hemorrhagic fever (DHF) in North Sumatra is a health problem that always occurs throughout the year. Based on the 2017 DHF report, Medan City is one of the regencies / cities that is included as a DHF endemic in North Sumatra. Karya Bakti Private Elementary School is one of the schools in the city of Medan. To solve this problem, community service activities are carried out in the form of training to increase students' knowledge about the prevention of DHF as well as the formation of larvae monitors. As for the number of training participants as many as 62 people coming from grade 5 students. School-age children are expected to be agents of change for the environment around their homes so that the incidence of DHF can be minimized. There is a difference in knowledge before and after training. While attitudes towards the prevention of DHF statistically showed no difference in knowledge before and after training.